Essential oils of cordiaspecies, compounds and applications : a systematic review - Andrade, Kellen Cruvinel Rodrigues (2021)
The purpose of this systematic review was to identify the available literature on the essential oil from species of genus Cordia. This study followed the Preferred Reporting Items for Systematic Reviews. The search was conducted on four databases: LILACS, PubMed, Science Direct, and Scopus until June 5th, 2020, with no time or language restrictions. Sixty out of the 1,333 initially gathered studies fit the inclusion criteria after the selection process. Nine species of Cordiawere reported in the selected studies, out of which 79% of the evaluated studies reported essential oil from Cordia curassavica. The essential oil extraction methods identified were hydrodistillation and steam distillation. As for biological application, antimicrobial, anti-inflammatory, larvicidal and antioxidant activities were the most reported. The main compounds reported for essential oil were β-caryophyllene, α-humulene, α-pinene, bicyclogermacrene, and sabinene. The information reported in this systematic review can contribute scientifically to the recognition of the importance of the genus Cordia.